Automated English mnemonic keyword suggestion for learning Japanese vocabulary - Anonthanasap, Orapin; Ketna, Monticha; Leelanupab, Teerapong (My University, 2015)
This paper proposes a new methodology that automatically generates English mnemonic keywords to support the learning of basic Japanese vocabulary. A new phonetic algorithm, called JemSoundex, is also introduced for phonetically transliterating the Japanese and English languages for phonetic matching. The effective mnemonic keywords are selected and ranked by considering their phonetic, orthographic and semantic similarities, as well as psycholinguistic power. A system-oriented evaluation is conducted to evaluate the proposed methodology, and in particular an approach on the basis of the JemSoundex algorithm. The experimental results show that the JemSoundex outperforms other comparative approaches, i.e., IPA, the original Soundex and Metaphone.
Keywords: Mnemonic Keywords; Phonetic Algorithm; Psycholinguistic Power